Myanmar : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This Article IV Consultation reports that Myanmar's authorities are moving forward with reforms of the exchange rate system. Priorities are establishing the market infrastructure for the planned move to a managed float, and monetary and foreign exchange policy capacity to complement plans to unify the exchange rates. Financial sector modernization remains essential to support the reform process and improve financial intermediation. Fiscal policy priorities include ending deficit monetization, reprioritizing spending, and increasing nonresource revenues for development spending within a medium-term fiscal framework.